The Advantages of Using Nucs in Beekeeping Operations - James D. Ellis; Catherine M. Zettel Nalen (EDIS)
ENY153, a 6-page illustrated fact sheet by James D. Ellis and Catherine Zettel Nalen, discusses the merits of nucleus colonies, which are smaller versions of full-sized Langstroth colonies — creating a nuc, rearing queens for nucs, reasons to use them, and problems associated with them. Published by the UF Department of Entomology and Nematology, September 2010.